Hubungan Pemberian Ice Breaking dengan Minat Belajar pada Siswa Kelas Tinggi - Muh Idris Jafar; Mujahidah Mujahidah; Riska Tamrin (Universtas Negeri Makassar, 2023)
Abstract. This research is a quantitative research with a correlational approach that aims to determine the relationship between giving Ice Breaking and learning interest in high school students at SD Negeri 363 Balielo, Bola District, Wajo Regency. with the number of respondents 47 people. Data collection is done by using a questionnaire. Data analysis technique with descriptive statistical analysis and inferential statistical analysis. Based on the results of descriptive statistical analysis, the results of ice breaking research have an average of 73.08 and a percentage of 73.08% in the good category and the average learning interest of high-class students has an average of 72.44 and a percentage of 72.44% in the good category. Based on the results of inferential statistical analysis, the tcount value (3.8421) is greater (>) the ttable value (1,67943) at a significance level of 5%. Thus H0 is rejected and H1 is accepted. The results of the study can be concluded that there is a significant relationship between the provision of Ice Breaking with learning interest in high grade students at SD Negeri 363 Balielo, Bola District, Wajo Regency. Abstrak: Penelitian ini adalah penelitian kuantitatif dengan jenis pendekatan korelasional yang bertujuan untuk mengetahui Hubungan Pemberian Ice Breaking dengan Minat Belajar pada Siswa Kelas Tinggi SD Negeri 363 Balielo Kecamatan Bola Kabupaten Wajo. dengan jumlah responden 47 orang. Pengumpulan data dilakukan dengan menggunakan angket. Teknik analisis data dengan analisis statistik deskriptif dan analisis statistik inferensial. Berdasarkan hasil analisis statistik deskriptif diperoleh hasil penelitian ice breaking memiliki rata-rata 73,08 dan persentase 73.08% dengan kategori baik dan rata-rata minat belajar siswa kelas tinggi memiliki rata-rata 72,44 dan persentase 72.44% dengan kategori baik. Berdasarkan hasil analisis statistik inferensial menunjukkan nilai thitung (3,8421) lebih besar (>) nilai ttabel (1,67943) pada taraf signifikansi 5%. Dengan demikian H0 ditolak dan H1 diterima. Hasil penelitian dapat disimpulkan bahwa terdapat hubungan yang signifikan antara Pemberian Ice Breaking dengan Minat Belajar pada Siswa Kelas Tinggi SD Negeri 363 Balielo Kecamatan Bola Kabupaten Wajo.Kata kunci: Ice breaking, minat belajar, siswa kelas tinggi